Field Carrying Capacity Analysis of Agricultural Sector Based Spatial in Nagari Taram, District of Lima Puluh Kota, West Sumatra - Ernamaiyanti Ernamaiyanti; Nur Irfan Asyari; Tiar Pandapotan Purba (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2016)
Land conversion has changed the field carryng capacity and filed quality. The purpose of this study is to figured out of field wideness Nagari Taram, and to analyze the availability and suitability of agricultural land Nagari Taram. Analysis of Field carrying capacity based on the Regulation of the Minister of Environment No. 17 of 2009, following by Focus Group Discussion (FGD) and analytic hierarchy process (AHP). The results, agricultural land based on type of ecosystem in the by area Nagari Taram is 1003.5 hectares consisting rice fields, dry land, ponds and open waters. Availability of agricultural land Nagari Taram is a surplus. stability of Nagari Taram slopes are low, high, less and medium. analysis showing field carrying suitability Nagari Taram is suitable for land agricultural.